Projected drought conditions in Northwest China with CMIP6 models under combined SSPs and RCPs for 2015–2099 - Su-Yuan Li; Li-Juan Miao; Zhi-Hong Jiang; Guo-Jie Wang; Kaushal Raj Gnyawali; Jing Zhang; Hui Zhang; Ke Fang; Yu He; Chun Li (Advances in Climate Change Research, 2020)
Northwest China is one of the most arid regions in the world and has experienced intriguing climate warming and humidification. Nonetheless, future climate conditions in Northwest China still remain uncertain. In this study, we applied an ensemble of the 12 latest model simulations of the Coupled Model Intercomparison Project Phase 6 (CMIP6) to assess future drought conditions until 2099 in Northwest China, as inferred from the Palmer Drought Severity Index (PDSI). Future drought conditions were projected under three climate change scenarios through the combination of shared socioeconomic pathways (SSPs) and representative concentration pathways (RCPs), namely, SSP126 (SSP1 + RCP2.6, a green development pathway), SSP245 (SSP2 + RCP4.5, an intermediate development pathway), and SSP585 (SSP5 + RCP8.5, a high development pathway). For 2015-2099, drought severity showed no trend under SSP126, in contrast, for the SSP245 and SSP585 scenarios, a rapid increase during 2015-2099 was observed, especially under SSP585. We also found that the drought frequency in Northwest China under SSP585 was generally lower than that under SSP126 and SSP245, although the drought duration under SSP585 tended to be longer. These findings suggest the green development pathway in drought mitigation and adaptation strategies in Northwest China, an arid and agricultural region along the Silk Road.
Keywords: 630; climate change; drought; CMIP6; PDSI; dryland; Northwest China